Defining health promoting sports coaches skills: A systematic review - Barros, K.; Vuillemin, A.; Rostan, F.; Lemmonier, F.; Guillemin, F.; Tezier, B.; Van Hoye, A. (International Journal of Sports Science & Coaching, 2025)
Sports coaches play a key role on sports participants` health, due to the informal educational dimension inherent to sport, but feel limited in terms of health promotion (HP) implementation in their practices. The aim of this systematic mapping review is to identify coaches` HP skills, which are already used in daily practice, and which they need to acquire, as well as leverages and barriers to their use. Based on PRISMA-P guidelines, six databases were searched using keywords close to sport coaching and skill and health. Inclusion criteria were 1) targeting organized grassroots sport coaches, 2) peer review English original articles, 3) discussing coaches` skills. Among the 2485 studies found, 56 were included based on a double-blind selection. Analysis included: thematic coding of skills, followed by a categorization based on health determinants (social, environmental, economic and organizational) mobilized and an analysis of the types of health (social, physical and psychological) affected. Results identified ten coach's HP skills: sport participant management, health support, education, evaluation, motivation, cooperation, prevention, communication, role modeling and self-management. These skills are mostly targeting sport participant psychological health. Barriers included coaches` own definition of the boundaries of their role, pressure from sport participants` relatives. Leverages to skills use were self-confidence, attending training, getting experience, increasing knowledge or adhering to guidelines. Coaches` HP skills are close both internal (e.g., self-management, role modeling) and external (in relations to sport participants or partners) and target mostly psychological health.